A Syntactic Analysis of English Noun Phrase Construction Difficulties in EFL Contexts - Annisa Nur Azizah; Tiara Fadiyah Rambe; Melani Melani; Siti Ismahani (Association of Islamic Education Managers (Permapendis) Indonesia, North Sumatra Province, 2025)
Mastering the syntactic properties of Noun Phrases (NPs) remains a major hurdle for Indonesian students learning English as a Foreign Language (EFL). This research aims to categorize typical syntactic errors made by these learners and evaluate how their native language (L1) structural logic interferes with English NP formation. By applying a syntactic analysis, the study contrasts the prenominal, right-branching framework of English with the head-initial, post-nominal patterns found in Indonesian. The investigation also considers the importance of syntax in cultivating Higher Order Thinking Skills (HOTS) and examines how the misuse of modifiers and determiners leads to predictable error patterns. The results indicate that students frequently transpose Indonesian word order onto English, resulting in systematic misorderings and omissions. Ultimately, this study offers pedagogical strategies for improving syntactic instruction to enhance linguistic precision and student participation in EFL settings.